Perception of emotion portrayal in cartoons by aurally and visually oriented people - Lindborg, PerMagnus (2010)
This article reports results from a study of perceived emotion portrayal in cartoons by different groups of subjects. A set of audiovisual stimuli was selected through a procedure in two steps. First, 6 ‘judges’ evaluated a large number of random snippets from all Mickey Mouse cartoons released between 1928 and -35. Analysis singled out the five films ranking highest in portraying respectively anger, sadness, fear, joy and love/tenderness. Subsequently, 4 judges made a continuous evaluation of emotion portrayal in these films, and six maximally unambiguous sequences were identified in each. The stimuli were presented to two groups (N=33), one in which the subjects were expected to be visually acute, and one where they would tend to be more aurally acute, in three different ways: bimodally (original) and unimodally, i.e as an isolated sound or video track. We investigated how group and modus conditions influenced the subjects’ perception of the relative intensity of the five emotions, as well as the sense of realism portrayed in the cartoon clips, and how amusing they were found to be. Finally, we developed an estimate for visual-aural orientation as a linear combination of select self-reported variables, and tested it as a predictor for the perception of medium dominance.